TINDAK TUTUR DALAM DRAMA BUZZER BEAT KARYA OMORI MIKA - Vidayanti, Reni (Jurnal Ilmiah Mahasiswa FIB, 2013)
The study, entitled the speech act in the drama Buzzer Beat Mika Omori's work is used to understand the function of speech acts and that is reflected in a drama. Speech act theory used in this study using the theory of Yule. This research uses descriptive qualitative method because the data collected is not a number, but a speech about the types and functions of speech acts in the drama Buzzer Beat Mika Omori analyzed works together - the same. The results in this study found the speech act locutions totaling 8 data, representative illocutionary speech acts numbered 6 Data, expressive illocutionary speech acts totaling 17 data 24 Data directive speech acts, illocutionary speech acts commissive totaling 13 data, the illocutionary speech act 2 data declarations and acts perlokusi said there are 10 data. Then also found 4 communication functions ie competitive, fun, cooperation and conflict. Key Word: Speech acts, pragmatics, Buzzer Beat